Family medicine in England (Colombia Medica, 1986)
Family Medicine, or general practice as primary health care is called in some countries, is a new specialization in Colombia, well-established after 40 years in England. Therefore, applying the best and most relevant aspects of the English system to Colombia would be good, considering her personnel and financial resources.